Kedudukan Nafkah Istri Nusyuz Selama Masa Idah (Studi KHI Pasal 80 Perspektif Fikih Munakahat) - Riska Wulandari; Muhammad Nirwan Idris; Jamaluddin, Jamaluddin (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This research aims to analyze Article 80 of the Compilation of Islamic Law (KHI) from the perspective of fiqh munakahat and to examine the views of scholars regarding the position of the living allowance for a nusyuz wife during the idah period. This study uses qualitative research methods with a normative juridical approach, which involves examining literature or secondary data as the primary basis for research by reviewing regulations and literature related to the issues being studied. The findings show that KHI Article 80 and fiqh munakahat share a fundamental principle regarding the living allowance for a nusyuz wife during the idah period, namely that a nusyuz wife is not entitled to a living allowance. However, there are differences in definitions, criteria, the process of proving nusyuz, as well as sanctions and impacts. The majority of scholars view that a nusyuz wife is not entitled to a living allowance and housing because the allowance is only obligatory in exchange for the wife's submission to her husband. The implications of this study highlight the need for a deeper understanding of Islamic teachings, strengthening public education and awareness, encouraging peaceful resolution through alternative channels, and monitoring and evaluating the implementation of marriage laws. These recommendations are expected to create a more harmonious and just marital environment based on the principles of justice and the protection of individual rights in accordance with Islamic teachings and applicable laws.